Ring-closing metathesis in peptides. Issue 39 (28th September 2016) - Gleeson, Ellen C.; Jackson, W. Roy; Robinson, Andrea J.
Graphical abstract: Highlights: Metathesis can be employed to stabilize peptide structure. Native disulfide bridges can be replaced with metabolically stable carbon-based bridges. Dicarba analogues can be used to elucidate mechanism of action of bioactive peptides. Abstract: This review highlights developments in the field of ring-closing metathesis applied to the synthesis of cyclic peptides. Special attention is focussed on the synthesis of dicarba peptides that mimic native cystine containing peptides. Recent advances in the field are discussed, including the stereoselective synthesis of carbon-bridged peptides and RCM in aqueous media.